Ökologische Klimatypen am Ostabfall der mexikanischen Meseta - Lauer, Wilhelm (ERDKUNDE, 1978)
The climatic map at the scale of 1:500 000 illustrates climatic types obtained from the altitudinal belts of temperature and the number of humid or arid months respectively. The methodical concept of this map is explained. The relationship between the climatic types and the vegetational division, as well as the ecological importance of the number of humid months or precipitation totals for individual types of vegetation respectively, are discussed. The special climatic phenomena are shown in an additional map at a scale of 1:1 500 000.